Tinjauan Perikatan Mudharabah Musytarakah dalam Asuransi Syariah - Juliani (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2023)
One of the sharia financial institutions that is experiencing very rapid development is sharia insurance. In sharia insurance there is a mudharabah musytarakah contract. The presence of this contract in sharia insurance in Indonesia is basically not explained in the Al-Qur'an and Sunnah. This research is a literature review, the reading sources consist of books, journals and fatwas relating to mudharabah musyarakah contracts in sharia insurance. This research uses a qualitative approach with descriptive methods. The analytical techniques are used to analyze the meaning contained in the data extracted through library sources. Based on fatwa Number 51/DSN-MUI/III/2006 concerning mudharabah musytarakah contracts on sharia insurance, there are no detailed arguments in the Al-Qur'an and Sunnah regarding halal, haram and syubhat laws regarding mudharabah musytarakah contracts on sharia insurance. However, its implementation must uphold the principles of Islamic law and fulfill the terms and conditions of engagement to avoid gharar, usury and maisir. This fatwa is a manifestation of the seriousness of law makers to develop contracts for sharia insurance institutions which aim to bring benefits.